Multipurpose stationary set / Muhammad Zulkhairee Md Zabani ... [et al.] - Md Zabani, Muhammad Zulkhairee; Norazman, Norshafiq Rizal; Hisyam, Wajihuddin; Mohd Hamzah, Muhammad Rezuan (2015)
The most common problem student's face in this fast pace technological world is that they always seem to forget to bring a complete set of stationaries. Not only that, they also tend to misplace their pens or any other stationaries or even loose them. By generating our idea of combining all of the essential stationary items into one pen hence, the multipurpose stationary set, not only it could save space because it is compact in size, have many functions in just one single pen. Not only it is light- weight but it is also easy to use or operate plus it is highly portable although it has many items in it. Furthermore the pen is user friendly and efficient. This project of us can help users in so many ways such as time, weight, space, easy to use, and highly portable. If this project of us functions well then we believe it has potential market value for investors.